2019
DOI: 10.1016/j.fusengdes.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Multi-model quantification of defects in irradiated lithium titanate

Abstract: Lithium based ceramics (Li 2 TiO 3 , Li 4 SiO 4 etc.) in the packed pebble form, used in breeder blankets to breed tritium, are promising candidates for future fusion reactors. Neutron induced trap sites in the ceramic breeder affect the diffusion and inventory of tritium and thereby influence the quantity of tritium recovered. In the present work, a multi model framework has been employed to quantify the number of defects, which can be used to evaluate trap-sites, due to neutron irradiation in porous Li 2 TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Lithium ceramics (Li 2 O, Li 2 ZrO 3 , Li 2 TiO 3 and Li 4 SiO 4 ) are considered as tritium multipliers (according to the 6 Li(n,He)T nuclear reaction) for use in the solid blanket of fusion reactors [7][8][9]. The two-phase lithium ceramic Li 2 TiO 3 -Li 4 SiO 4 combines the chemical stability of Li 2 TiO 3 and the high density of lithium in Li 4 SiO 4 [8,10,11]. Studies of lithium silicates (Li 4 SiO 4 and Li 2 SiO 3 ) have shown that these materials have good tritium solubility, they are compatible with structural materials and have sufficient thermophysical, chemical and mechanical stability at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium ceramics (Li 2 O, Li 2 ZrO 3 , Li 2 TiO 3 and Li 4 SiO 4 ) are considered as tritium multipliers (according to the 6 Li(n,He)T nuclear reaction) for use in the solid blanket of fusion reactors [7][8][9]. The two-phase lithium ceramic Li 2 TiO 3 -Li 4 SiO 4 combines the chemical stability of Li 2 TiO 3 and the high density of lithium in Li 4 SiO 4 [8,10,11]. Studies of lithium silicates (Li 4 SiO 4 and Li 2 SiO 3 ) have shown that these materials have good tritium solubility, they are compatible with structural materials and have sufficient thermophysical, chemical and mechanical stability at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Several concepts of test blanket modules based on lithium ceramics are being developed for testing at the ITER reactor [1]. Lithium metatitanate Li 2 TiO 3 has good tritium release parameters, as well as good thermal and thermomechanical characteristics [2,3]. The most important property of lithium ceramics Li 2 TiO 3 is its ability to withstand exposure to long-term high-energy radiation at high temperatures and across large temperature gradients.…”
Section: Introductionmentioning
confidence: 99%